Maker-centered learning : empowering young people to shape their worlds - Clapp, Edward P.; Ross, Jessica, 1966-; Ryan, Jennifer Oxman, 1974-; Tishman, Shari (Jossey-Bass ; John Wiley & Sons, 2016)
The Agency by Design guide to implementing maker-centered teaching and learning Maker-Centered Learning provides both a theoretical framework and practical resources for the educators, curriculum developers, librarians, administrators, and parents navigating this burgeoning field. Written by the expert team from the Agency by Design initiative at Harvard's Project Zero, this book -Identifies a set of educational practices and ideas that define maker-centered learning, and introduces the focal concepts of maker empowerment and sensitivity to design.-Shares cutting edge research that provides evidence of the benefits of maker-centered learning for students and education as a whole.-Presents a clear Project Zero-based framework for maker-centered teaching and learning -Includes valuable educator resources that can be applied in a variety of design and maker-centered learning environments -Describes unique thinking routines that foster the primary maker capacities of looking closely, exploring complexity, and finding opportunity. A surge of voices from government, industry, and education have argued that, in order to equip the next generation for life and work in the decades ahead, it is vital to support maker-centered learning in various educational environments. Maker-Centered Learning provides insight into what that means, and offers tools and knowledge that can be applied anywhere that learning takes place.